Tinjauan Filosofis dalam Tradisi Upacara Selametan Mitoni dan Sajian Nasi Tumpeng: Studi Deskriptif di Desa Sumurugul Kecamatan Wanayasa Kabupaten Purwakarta - Imas Nurazizah (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
The purpose of this study is to review the philosophical review in the tradition of the Mitoni Selamattan ceremony and Nasi Tumpeng as a descriptive study in Sumurugul Village, Wanayasa District, Purwakarta Regency, West Java. This research is a qualitative research using phenomenological descriptive method and philosophy of value as an analytical knife. The main topics of discussion are the history of the Mitoni tradition and the Nasi Tumpeng dish, the public's understanding of the Mitoni salametan tradition; and the philosophical review contained in the Mitoni tradition is dissected through Roland Barthes' semiotic theory and Schwartz's philosophy of value. The findings in this research show that Mitoni's salvation has become a tradition of the Muslim community in Sumurugul Village accompanied by Islamic values in it, the purpose of holding this salvation is to ask for blessings to the Almighty so that both the mother and the baby in her womb are given safety. Observing the overall findings in the field, it is not an exaggeration if the author concludes that this tradition is a tradition that has experienced acculturation from Islamic religious culture in the Sumurugul village community.